Migrações dos indígenas Warao e proteção de direitos humanos pelo constitucionalismo latino-americano no Brasil - Fortes, Antônio Corrêa Cortes (2023)
The work is limited to the migrations of indigenous Venezuelans of the Warao ethnic group to Brazil in the context of the interculturality proposed in Latin American constitutionalism. This, as a possible epistemic alternative in the face of migratory flows between Venezuelan and Brazilian territories. Modernity and Eurocentrism responsible for the process of colonization of the Americas caused centuries of imposition of an oppressive and homogenizing rationality. The political spaces of identity formation of peoples and their cultures suffered with the concealment of the Other. Current forced displacements presuppose the capitalist neoliberal model, preceded by modernity and its institutions. In the last five hundred years, ancient traditional peoples of Latin America have been suffering from genocide, xenophobia, racism and the exclusion of what is different. In contrast, since the end of the 20th century, a new constitutionalism has emerged in Latin America and breaks paradigms with the traditional model of national states, which have been based for five centuries on cultural homogenization, from a Eurocentric perspective. In this context, the research investigates legal responses from the episteme of the new Latin American constitutionalism to the migrations of the Warao indigenous peoples. The research aims to examine Latin American constitutionalism and how autonomies linked to the idea of protecting traditional peoples are developed, especially legal pluralism and intercultural democracy, based on the reality of mobility experienced by the Warao indigenous population. The research will be carried out through the analytical method worked by Enrique Dussel, explained mainly in the work Method for a Philosophy of Liberation (1986). The basic theory contemplates enough theoretical density to contain in itself the adequate methodological proposal for the development of the present research. Therefore, the investigation will take place with studies in Latin America and focus on modernity, coloniality and decoloniality. As for the data, the research explores official reports that deal specifically with the mobility of the Warao and their most relevant statistical information.